Antibody Engineering - Böldicke, Thomas (IntechOpen, 2018)
Antibody Engineering comprises in vitro selection and modification of human antibodies including humanization of mouse antibodies for therapy, diagnosis, and research. This book comprises an overview about the generation of antibody diversity and essential techniques in antibody engineering: construction of immune, naive and synthetic libraries, all available in vitro display methods, humanization by chain shuffling, affinity maturation techniques, de novo synthesis of antibody genes, colony assays for library screening, construction of scFvs from hybridomas, and purification of monoclonal antibodies by exclusion chromatography. In addition, other topics that are discussed in this book are application and mechanism of single domain antibodies, structural diversity of antibodies, immune-mediated skin reactions induced by TNF-alpha recombinant antibodies, and bioinformatic approaches to select pathogen-derived peptide sequences for antibody targets.